Odpowiedzi

2009-11-28T12:40:36+01:00
A) ( 3x - 2)( 3x - 2y + 1) - 4x ( 2x - 3y + 1) =
=9x²-6xy +3x - 6x+4y -2 - 8x² +12xy - 4x =
x² +6xy-7x +4y - 2

b) 2 ( m + 1) ( n - 2) + 2 ( n +1) ( m - 2) =
=2(mn - 2m + n - 2) + 2( mn - 2n + m - 2)
=2mn -4m +2n -4 + 2mn -4n +2m -4 =
=4mn- 2m- 2n - 8

c) x ( x + 1) ( x + 2) - x ( x -1) ( x - 2)=
= x(x²+2) - x(x²+2) =
x³+ 2x -x³ - 2x = 0

:))
2009-11-28T12:53:02+01:00
A) (3x-2)(3x-2y+1)-4x(2x-3y+1)=
9x²-6xy+3x-6x+4y-2-8x²+12xy-4x=
x²+6xy-7x+4y-2
b) 3(m+1)(n-2)+2(n+1)(m-2)=
3(mn-2m+n-2)+2(mn-2n+m-2)=
3mn-6m+3n-6+2mn-4n+2m-4=
5mn-4m-n-10
c) x(x+1)(x+2)-x(x-1)(x-2)
x(x²+2x+x+2)-x(x²-2x-x+2)
x³+2x²+x²+2x-x³+2x²+x²-2x=
6x²